Pathophysiological characteristics of non-alcoholic steatohepatitis-like changes in cholesterol-loaded type 2 diabetic rats - Toriniwa, Y; Muramatsu, M; Ishii, Y; Riya, E; Miyajima, K; Ohshida, S; Kitatani, K; Takekoshi, S; Matsui, T; Kume, S; Yamada, T; Ohta, T (Physiological research, 2018)
Spontaneously Diabetic Torii (SDT) fatty rats, a new obese diabetic model, reportedly presented with features of non-alcoholic steatohepatitis (NASH) after 32 weeks of age. We tried to accelerate the onset of NASH in SDT fatty rats using dietary cholesterol loading and noticed changes in the blood choline level which is expected to be a NASH biomarker. Body weight and biochemical parameters were measured from 8 to 24 weeks of age. At 16, 20, 24 weeks, pathophysiological analysis of the livers were performed. Hepatic lipids, lipid peroxides, and the expression of mRNA related to triglyceride (TG) synthesis, inflammation, and fibrosis were evaluated at 24 weeks. Hepatic fibrosis was observed in SDT fatty rats fed cholesterol-enriched diets (SDT fatty-Cho) from 16 weeks. Furthermore, hepatic lipids and lipid peroxide were significantly higher in SDT fatty-Cho than SDT fatty rats fed normal diets at 24 weeks. Hepatic mRNA expression related to TG secretion decreased in SDT fatty-Cho, and the mRNA expression related to inflammation and fibrosis increased in SDT fatty-Cho at 24 weeks. Furthermore, SDT fatty-Cho presented with increased plasma choline, similar to human NASH. There were no significant changes in the effects of feeding a cholesterol-enriched diet in Sprague-Dawley rats. SDT fatty-Cho has the potential to become a valuable animal model for NASH associated with type 2 diabetes and obesity.
Keywords: krysa rodu Rattus; Cholesterol, Dietary; Diabetes Mellitus, Type 2; nealkoholová steatóza jater; diabetes mellitus 2. typu; cholesterol dietní; Animals; ženské pohlaví; Rats, Sprague-Dawley; Rats; zvířata; potkani Sprague-Dawley; Non-alcoholic Fatty Liver Disease; Female